PENGARUH STRATEGI PEMASARAN TERHADAP MINAT BERKUNJUNG PADA DUNGUS FOREST PARK DI MADIUN - Aprizeila Rizky Geraldine; Rizal Ula Ananta Fauzi; Apriyanti Apriyanti (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2022)
This purpose of this reserch was to determine: (1) The effect of the product on interest in visiting Dungus Forest Park in Madiun. (2) The influence of place on interest in visiting Dungus Forest Park in Madiun. (3) The effect of price on interest in visiting Dungus Forest Park in Madiun. (4) The effect of promotion on interest in visiting Dungus Forest Park in Madiun. (5) The effect of product, place, price, and promotion on interest in visiting Dungus Forest Park in Madiun. The method in this study uses quantitative methods. The data collection method uses questionnaires, interviews, observations, and documentation. Meanwhile, the data analysis used descriptive statistical analysis, data instrument test, classical assumption test, multiple regression line analysis, and multiple determinant coefficient (R2). The results showed that: (1) There was a significant effect of the product on interest in visiting the Dungus Forest Park in Madiun. (2) There is a significant influence of place on interest in visiting Dungus Forest Park in Madiun. (3) There is a significant effect of price on interest in visiting Dungus Forest Park in Madiun. (4) There is a significant effect of promotion on interest in visiting Dungus Forest Park in Madiun. (5) There is a significant effect of product, place, price, and promotion on interest in visiting Dungus Forest Park in Madiun.